Synthesis of cerium-doped yttrium aluminum garnet nanopowder low-temperature reaction combustion method - Chung, Do Ngoc; Dinh, Nguyen Nang; Hieu, Do Ngoc; Duong, Pham Hong (VNU Journal of Science: Mathematics - Physics; Vol 28 No 2, 2012)
Abstract. Nanopowders of cerium doped yttrium aluminum garnet (Y 3 Al 5 O 12 :Ce 3+ ) - YAG:Ce were prepared by low-temperature sol-gel method. High-purity Y 2 O 3 , Al(NO 3 ) 3 .9H 2 O, Ce(NO 3 ) 3 ·6H 2 O in the presence of citric acid as complexing agent were used as initial  materials. The YAG:Ce nanopowders were characterized using X-ray diffraction, SEM, dynamic light scattering particle size analyzer and a high resolution spectrometer-Microspec-235b. The particle sizes of the YAG:Ce powder were estimated from SEM image and dynamic light scattering particle size analyzer to be 4 – 80 nm. The annealing effect on the crystalline structure of the samples was reported. Keywords: YAG:Ce nanopowder; Sol-Gel method; Photoluminescence (PL).